Maqāṣid al-‘Ilm and Maqāṣid al-Bī’ah: A Dialogue between the Philosophy of Science and Ecotheology in the Environmental Crisis - Husnul Haetami; Abdul Fattah; Syamsul Arifin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
The contemporary environmental crisis—marked by ecological degradation, climate change, and a weakening of ethical responsibility toward nature—demands a renewed integration between scientific knowledge and spiritual consciousness. This study examines the dialogical relationship between Maqāṣid al-‘Ilm (the higher objectives of knowledge) and Maqāṣid al-Bī’ah (the higher objectives of environmental stewardship) within the encounter of the philosophy of science and Islamic ecotheology to formulate an ethical–epistemic framework for ecological responsibility. Employing a qualitative descriptive approach through systematic literature review, philosophical document analysis, and thematic synthesis of classical and contemporary Islamic sources alongside ecotheological and scientific-philosophical discourses, this research develops an integrative conceptual model linking objectives of knowledge with environmental ethics. The findings indicate that Maqāṣid al-‘Ilm prioritizes wisdom-oriented knowledge grounded in moral refinement and the preservation of life, while Maqāṣid al-Bī’ah emphasizes ecological balance (mīzān), environmental justice (‘adl al-bī’ah), and protection of creation as expressions of worship and stewardship (khilāfah). Their dialogical integration reveals that scientific knowledge detached from ethical and spiritual foundations tends to exacerbate environmental degradation, whereas knowledge rooted in ecotheological awareness fosters holistic ecological consciousness that unites rational inquiry, moral responsibility, and spiritual devotion. The study concludes that integrating these two maqāṣid offers a transformative epistemological paradigm for reorienting the human role as moral agent and khalīfah of the earth, contributing to the development of environmentally responsible scientific practice, spiritually grounded education, and sustainable worldviews capable of responding effectively to the ecological crisis